Instant Controlled Pressure Drop (D.I.C.) in Food Processing From Fundamental to Industrial Applications - Allaf, Tamara.; Allaf, Tamara.; Allaf, Karim.; Allaf, Karim. (Food Engineering Series,, 2014)
The use of Instant Controlled Pressure Drop (D.I.C.) in food processing operations is relatively new when compared with other conventional or innovative technologies. In addition to existing applications such as drying, texturing and decontamination, D.I.C. technology has been shown to be highly appropriate for an ever-growing number of uses and with a wide range of raw materials. Some examples are post-harvesting and drying of fruits and vegetables; cereal steaming; extraction of essential oils and active molecules, where D.I.C. may be combined with supercritical fluids, ultrasound or microwaves; and the hydrolysis of cellulose and the transesterification of lipids. This book presents a complete picture of current knowledge on the use of D.I.C. in food processing, preservation and extraction. It provides a comprehensive compilation, summarizing the fundamentals of D.I.C. technology, current developments, new research findings, safety precautions and environmental impacts. It will also contribute to widening the scope of D.I.C. technology through the inclusion of some much-needed examples of industrial applications. Each chapter of the book is complementary to the other chapters. They all are based on presentations of reputed international researchers and address the latest progress in the field.    Professor Karim ALLAF heads a research team working on the intensification of eco-processes at La Rochelle University. He is a physicist and an expert in the thermodynamics of “instantaneity”. Dr. Tamara ALLAF is the R&D manager of ABCAR-DIC Process Company. A chemical engineer, she obtained her Ph.D. in innovative extraction processes.